THE CHANGING EPIDEMIOLOGY OF HEPATITIS B VIRUS INFECTION IN THE CANADIAN NORTH - MINUK, G. Y.; LING, N.; POSTL, B.; WAGGONER, J. G.; NICOLLE, L. E.; HOOFNAGLE, J. H. (Oxford University Press, 1985)
Hepatitis B virus infections are common in the Eskimo (Inuit) populations of the world. In this study, serologic markers of hepatitis B infection were measured in 172 inhabitants (78%) of an isolated Canadian inuit settlement. Evidence of hepatitis B infection was found in 22% of residents. The prevalence increased with age, being uncommon under the age of 20 (7%), yet present in the majority of inhabitants over the age of 40 (64%). Sera from four individuals (2.3%) were hepatitis B surface antigen- (HBsAg) positive. All four HBsAg carriers were negative for immunoglobulin M (lgM) antibody to hepatitis B core antigen (lgM anti-HBc), hepatitis B e antigen (HBeAg), and DNA polymerase, but positive for antibody to hepatitis B e antigen (anti-HBe). These data suggest that hepatitis B infection has become relatively uncommon in the inhabitants of this community born during the past 20–30 years. The apparent decline in prevalence did not appear to be related to recent demographic or socioeconomic changes in the area.